A new eilenodontine (Lepidosauria, Sphenodontidae) from the Lower Cretaceous of Central Patagonia - Carballido, José Luis (2014)
A new species of eilenodontine sphenodontian, Priosphenodon minimus, is described from a locality 400 km south of those that yield the northern Patagonian eilenodontines (the largest known terrestrial sphenodontians). The new species, represented by subadult specimens, is both the smallest known eilenodontine and the southernmost record of the group. Pr. minimus is characterized by a nearly vertical lateral process of the premaxilla; anteriorly extended frontals that lack the naso-prefrontal projections; a rounded frontal anterior process; a prefrontal that posteriorly embraces the nasal; a coronoid process of the dentary that is tall and with an anterior border that is vertical in medial view; strong anteromedial ﬂanges on all teeth; uncommonly dense dental packing; and an anteriorly extended angular that reaches the midlength of the lower jaw. Differences from juvenile specimens of Priosphenodon avelasi, such as the interruption of the prefrontaljugal contact, are marked. The holotype and associated material come from early Albian strata, and are therefore around 12 million years older than the northern Patagonian giant sphenodontians. The new species here described reveals that many of the characters used to diagnose Kaikaiﬁlusaurus calvoi are widespread, so this taxon should be regarded as a nomen dubium. Therefore, the genus Priosphenodon is considered as valid herein, with the new species assigned to it. A phylogenetic analysis demonstrates the monophyly of Priosphenodon and suggests that the new taxon represents an incidence of dwarﬁng. This discovery increases the morphological disparity among these specialized herbivores, and provides new climatological and biostratigraphic information on the terrestrial ecosystems of Patagonia.